Pemanfaatan Limbah Mikroorganisme Anaerob Proses Biogas Menjadi Pupuk Organik Padat - Erda Roriza Putri Redina; Niken Febrila Awardani; Ketut Sumada (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
The production process of biogas, which utilizes anaerobic biological processes, not only results in biogas but also produces slurry in the form of microorganism waste over time. The increasing number of anaerobic microorganism processes presents challenges that make it inadvisable to directly dispose of this anaerobic microorganism waste into the environment, as it has the potential to be a pollutant. Environmental management efforts can involve utilizing this waste to create solid organic fertilizer. This is due to the fact that the waste contains essential nutrients for plants, including nitrogen (N), carbon (C), phosphorus (P), potassium (K), calcium (Ca), magnesium (Mg), copper (Cu), and zinc (Zn). Despite the presence of both macromolecular and micromolecular organic matter, the C-organic content of anaerobic microorganism waste exceeds the minimum standard for solid organic fertilizer C/N ratio of 25, with a value of 49.62. A variety of techniques may be employed to reduce the C-organic content of anaerobic microorganism waste, including aerobic composting. The objective of this research is to ascertain the C-organic (C) and nitrogen (N) content in the solid organic fertilizer produced and to gain insight into the influence of air flow rate (oxygen) (liters/minute) and composting time (days) on the quality of the solid organic fertilizer produced. The findings of the study indicate that an increase in composting time results in a reduction in the C/N ratio, with a stabilization observed during a seven-day composting period, exhibiting a C/N ratio value of 18.05. An increase in the air flow rate results in a notable reduction in the C/N ratio. The greatest reduction, amounting to 65.85%, was observed when an air flow rate of 8.5 L/minute was employed.